Mortality, survival and prognostic factors of people with AIDS in intensive care unit - Gilmara Holanda da Cunha; Reângela Cíntia Rodrigues de Oliveira Lima; Marcos Venícios de Oliveira Lopes; Marli Teresinha Gimeniz Galvão; Larissa Rodrigues Siqueira; Marina Soares Monteiro Fontenele (SciELO, 2021)
ABSTRACT Objective: To analyze mortality, survival and prognostic factors of patients with AIDS in Intensive Care Unit (ICU). Method: Retrospective cohort study with a sample of 202 patients with AIDS in ICU, whose sociodemographic, epidemiological, and clinical characteristics were obtained from medical records and assessed. Results: Patients were mostly male (73.8%) and drug users (59.4%), with no regular health follow-up (61.4%) and no adherence to antiretrovirals (40.6%), presenting low CD4+ T lymphocyte count (94.0%) and high viral load (44.6%). The main causes of hospitalization were sepsis and respiratory and renal insufficiency. The mean duration of hospitalization was 11.9 days (p = 0.0001), with a 41.6% survival; 58.5% died in the ICU. Sepsis upon admission (p < 0.001), pressure injury (p = 0.038), sexual exposure (p = 0.002), high viral load (p = 0.00001) and prolonged hospitalization (p < 0.001) increased the risk of death. Conclusion: Most patients had no regular health follow-up, were drug users and presented low CD4+ T lymphocyte count and high viral load. The high mortality indicated that antiretroviral adherence is essential to reduce viral resistance, opportunistic diseases, and mortality.